Mathematical challenges II, plus six : selected problems from the Mathematics student journal - Hill, Thomas J. (National Council of Teachers of Mathematics, 1974)
One hundred problems in algebra, geometry, number theory, probability, and trigonometry, varying in difficulty. Solutions are included as well as six articles on mathematics.